Possible health danger associated with garbage/refuse collectors - Mohammed, Sani; Abdul Latif, Puziah (International Organization of Scientific Research, 2014)
Wastes collectors refer to group of people who collects solid waste generated in various areas for disposal at designated locations. The service is usually provided by responsible contractors assigned to schedule areas. In advanced nations such as Europe and the USA, automated trucks are used in collection and disposal of waste using hydraulic lifts. The opposite is applied in developing countries such as Malaysia. Wastes collectors in the study area are manually collecting the waste before lifting it on the operational trucks. Manual waste collection service is associated with health danger. The workers are exposed to odors, and they can dirty their cloths easily as result of non-usage of protective gears. Other health danger includes injuries from broken glasses, musculoskeletal disorder and diseases that accompany solid waste. The aim of this project was to determine whether the workers are exposed to the work practices, injuries, musculoskeletal disorder and other danger faced by Malaysian refused collectors in carrying out their responsibilities. The sample for the study constituted thirty (30) solid waste collectors selected through convenient sampling technique. Data for the study was collected through a structured questionnaire on Malaysian refused collectors and visual observation. Responses were analyzed using descriptive statistics. Results revealed that out of the total respondents 56.6% disagreed and strongly disagreed that collectors always make use of their protective material at work, 10% were neutral while 33.3% agreed and strongly agreed. This implied that majority of the collectors have no access to personal protective equipment which is contrary to OSHA requirements. The study therefore concludes that solid waste collectors experienced different types of preventable dangers inherent in their duty due to their work practice.